PENGARUH PEMBELAJARAN PENGAJUAN MASALAH PADA PEMAHAMAN KONSEP MATEMATIKA DAN KETERAMPILAN BERPIKIR KRITIS UNTUK SISWA KELAS 8 - Suci Nurhandayani (Program Studi PGSD Universitas Flores, 2022)
The purpose of this study was to determine the effect of problem-posing learning on understanding mathematical concepts and critical thinking skills of grade 8 students. Research design used a quasi-experimental design with pretest-posttest nonequivalent control group design. .T-test was used to determine the effect of understanding mathematical concepts, while to determine the effect of students' critical thinking skills was a non-parametric of Mann Whitney test. Results of study reported that percentage of the average N-Gain value for understanding mathematical concept of an experimental class was 31.47 and control class was 24.40, while the average percentage of the N-Gain value of students' critical thinking skills in an experimental class was 27.11 and the control class was 12.76. The results show the effect of understanding mathematical concepts and students' critical thinking skills. Other results showed that students' responses who received problem-posing learning was 64.21% better than the class that received conventional learning. Student’s activities who study by posing problems are more active with an average of 62.51% compared to students who study conventionally with an average of 36.25%.